Investigation UV-treatment and surface modifications effect on surface energy and aging behaviour of biomedical surfaces - Bulutsuz, Asli Gunay (INDERSCIENCE ENTERPRISES LTD, 2020)
Biomedical Ti6Al4V Eli alloy discs were subjected to blasting, anodisation and ultra viola (UV) treatments under the same manufacturing conditions with implants. These different surface modification effects on topography and wetting performance were investigated in detail with optical tensiometer for autoclaved and non-autoclaved samples. Surface contact angle changes after packing of the surfaces were investigated for initial, 1 and 3 months later. The topographical investigation by scanning electron microscope (SEM) showed that blasted 350 V had the mean 1.842 +/- 102 nm pores size and blasted 280 V treated surfaces had the mean 771 +/- 85 nm pore size. Autoclaving decreased wettability capabilities of all surfaces, especially for the blasted specimen group. According to the repetitive measurement results, after the 1st month the wettability's of the surfaces were similar compared to the initial. After the 3rd month, a decreasing trend was observed for wetting capability. But beyond all groups, the contact angle was the same with non-UV treated state for the blasted 350 V group after 3rd month.
Keywords: ultra viola treatment; anodisation; autoclaving; contact angle; aging behaviour; implants; IMPLANT SURFACES; TITANIUM; TIME; OSSEOINTEGRATION; WETTABILITY; OSTEOBLAST; STEEL; STERILIZATION; EXPRESSION; RESPONSES; Engineering; Materials Science; Physics